Mechanical Stress-Induced IGF-1 Facilitates col-I and col-III Synthesis via the IGF-1R/AKT/mTORC1 Signaling Pathway. (6th December 2021) - Yan, Bin; Zeng, Canjun; Chen, Yuhui; Huang, Minjun; Yao, Na; Zhang, Jie; Yan, Bo; Tang, Jiajun; Wang, Liang; Zhang, Zhongmin
Abstract : Mechanical stress promotes human ligamentum flavum cells (LFCs) to synthesize multitype collagens, leading to ligamentum flavum hypertrophy (LFH). However, the mechanism of mechanical stress in the formation of collagen remains unclear. Therefore, we investigated the relationship between mechanical stress and collagen synthesis in the present study. First, LFCs were isolated from 9 patients and cultured with or without mechanical stress exposure for different times. IGF-1, collagen I (col-I), and collagen III (col-III) protein and mRNA levels were then detected via ELISA and qPCR, respectively. Moreover, the activation of pIGF-1R, pAKT, and pS6 was examined by Western blot analysis. To further explore the underlying mechanism, an IGF-1 neutralizing antibody, NVP-AEW541, and rapamycin were used. IGF-1, col-I, and col-III were significantly increased in stressed LFCs compared to nonstressed LFCs. In addition, the activation of pIGF-1R, pAKT, and pS6 was obviously enhanced in stressed LFCs. Interestingly, col-I protein, col-I mRNA, col-III protein, col-III mRNA, and IGF-1 protein, but not IGF-1 mRNA, were inhibited by IGF-1 neutralizing antibody. In addition, col-I and col-III protein and mRNA, but not IGF-1, were inhibited by both NVP-AEW541 and rapamycin. Moreover, the activation of pIGF-1R, pAKT, and pS6 was reduced by the IGF-1 neutralizing antibody and NVP-AEW541, and the activation of pS6 was reduced by rapamycin. In summary, these results suggested that mechanical stress promotes LFCs to produce IGF-1, which facilitates col-I and col-III synthesis via the IGF-1R/AKT/mTORC1 signaling pathway.